On the Role of Thermospheric Winds and Sporadic E Layers in the Formation and Evolution of Electrified MSTIDs in Geomagnetic Conjugate Regions. Issue 8 (25th August 2018) - Narayanan, V. L.; Shiokawa, K.; Otsuka, Y.; Neudegg, D.
Abstract: The electrified medium‐scale traveling ionospheric disturbances (EMSTIDs) occurring as geomagnetically conjugate features in the middle latitude F region ionosphere are studied using multi‐instrument observations. Airglow imaging of OI 630 nm emission over Sata, Japan, and Darwin, Australia, are used to identify the occurrence of EMSTIDs. Thermospheric wind measurements made with the Fabry‐Perot interferometer observations of OI 630 nm from Shigaraki, Japan, and Darwin, Australia, are used along with ionosonde observations over Yamagawa, Japan, and Darwin, Australia, to study the thermospheric and ionospheric characteristics. These are the first results from such multi‐instrument observations simultaneously made from geomagnetic conjugate locations. Our results show that the amplitudes of the EMSTIDs are often different between the hemispheres. Thermospheric meridional winds appear to control the EMSTID amplitudes in the respective hemisphere. However, EMSTIDs are generated only when there is significant sporadic E activity with foEs often reaching greater than 6 MHz and (foEs − fbEs) reaching above 5 MHz at least for a short duration occurred. Existence of strong sporadic E activity on one of the hemispheres is found to be sufficient enough for generation of EMSTIDs in the conjugate F regions. These results conclusively indicate the importance of sporadic E layers in the generation of EMSTIDs. Further, it shows the significance of interhemispheric coupling between the E and F region ionospheres in the formation of EMSTIDs while their amplitudes in the respective hemispheres appear to have control of thermospheric neutral winds in the same hemisphere. Key Points: Presence of significant sporadic E activity in at least one of the hemisphere is found to be necessary for formation of EMSTIDs EMSTIDs form even when thermospheric winds are not favorable in one hemisphere as hemisphere coupled U × B electric fields are important Amplitudes of EMSTIDs often differ between the hemispheres based on the thermospheric meridional winds